Scalar implicatures: working memory and a comparison with only - Marty, Paul P.; Chemla, Emmanuel (Frontiers in Psychology, 2013)
A Scalar Implicature (SI) arises when the use of a weaker expression (e.g., some politicians are corrupt) implies the denial of an alternative sentence (e.g., not all politicians are corrupt). The cognitive effort associated with the processing of SIs involves central memory resources (De Neys & Schaeken 2007, Dieussaert et al. 2011, Marty et al. 2013). The goal of this study is to locate this previous result within the current psycholinguistic debate, and to understand at which level of SI processing these resources are specifically involved. Using a dual-task approach, we show that (i) tapping participant's memory resources interferes with the derivation of SIs, whereas (ii) it does not affect the interpretation of sentences with `only' involving similar mechanisms (e.g., only some politicians are corrupt). We explain how these findings suggest that the central memory resources are not involved in the core process at the source of SIs, and discuss how this new difference between SIs and `only' bears on recent linguistic debates on the division of labour between grammar and pragmatics.